DEVELOPMENT OF PROBLEM-BASED LEARNING INSTRUCTIONAL VIDEOS ON UNIFORM AND UNIFORMLY ACCELERATED LINEAR MOTION FOR JUNIOR HIGH SCHOOL STUDENTS: Pontianak, Indonesia - Nur Oktivianti Dewi; Eny Enawaty; Ari Widiyantoro; Dede Suratman; Haratua Tiur Maria S (Jurnal Math-UMB.EDU, 2026)
Physics learning at the junior secondary school level on the topics of Uniform Linear Motion and Uniformly Accelerated Linear Motion often shows low conceptual understanding due to limited use of contextual and visual instructional media. This study aims to develop and examine the effectiveness of Problem-Based Learning (PBL) instructional videos in improving students’ conceptual understanding. The research employed a Research and Development approach using the ADDIE model and adopted a pre-experimental design with a one-group pretest–posttest involving 36 students as trial subjects. The instruments included expert validation sheets, conceptual understanding tests, and student response questionnaires. Data were analyzed using descriptive statistics, normality tests, paired-sample t-tests, and N-Gain analysis. The results showed that the instructional video product was categorized as highly feasible based on expert validation and student responses (89.7%). The students’ mean scores increased from 57.97 to 69.44, with a reduction in variance and standard deviation, indicating a more even distribution of conceptual understanding. The normality test confirmed that the data were normally distributed, and the paired-sample t-test revealed a significant difference between pretest and posttest scores (p < 0.001). The N-Gain value of 0.27 was in the low–moderate category, indicating initial effectiveness. Therefore, the developed PBL instructional videos indicate initial effectiveness in enhancing students’ conceptual understanding and can be considered a feasible instructional innovation for junior secondary school physics learning. Keyword: learning video, Problem-Based Learning, conceptual understanding, junior high school physics, instructional innovation